2019
DOI: 10.1002/biof.1598
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis and bone remodeling: A focus on growth factors and bioactive peptides

Abstract: Bone is one of the most frequently transplanted tissues. The bone structure and its physiological function and stem cells biology were known to be closely related to each other for many years. Bone is considered a home to the well‐known systems of postnatal mesenchymal stem cells (MSCs). These bone resident MSCs provide a range of growth factors (GF) and cytokines to support cell growth following injury. These GFs include a group of proteins and peptides produced by different cells which are regulators of impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 175 publications
1
54
0
Order By: Relevance
“…Toosi et al precisely described in a review a range of growth factors and cytokines provided by bone resident MSCs to support cell growth following injury and demonstrated how GF signaling plays a critical role in regulating osteogenesis, chondrogenesis and bone/mineral homeostasis [57]. It is known that the delivery of exogenous GFs, i.e., BMP-2, to the non-union bone fracture site remarkably improves healing results [58].…”
Section: Conditioning Systems Composites and Growth Factorsmentioning
confidence: 99%
“…Toosi et al precisely described in a review a range of growth factors and cytokines provided by bone resident MSCs to support cell growth following injury and demonstrated how GF signaling plays a critical role in regulating osteogenesis, chondrogenesis and bone/mineral homeostasis [57]. It is known that the delivery of exogenous GFs, i.e., BMP-2, to the non-union bone fracture site remarkably improves healing results [58].…”
Section: Conditioning Systems Composites and Growth Factorsmentioning
confidence: 99%
“…Increasing the efficiency of directional MCS osteogenic differentiation has long been a central issue in bone tissue engineering. Most recent studies have focused on using exogenous biochemical cues, e.g., growth factors, whose use in bone defect repair has aroused clinical safety concerns 2 . Leveraging physical factors in bone tissue engineering scaffolds to induce MCS osteogenic differentiation opens a new door for addressing this issue.…”
Section: Resultsmentioning
confidence: 99%
“…One of those hurdles is controlling the directional osteogenesis differentiation of stem cells seeded in the scaffold, which is still inadequate. Conventional approaches involve using substantial amounts of osteoinductive growth factors or other chemicals, which lack efficiency for osteogenesis induction and might raise safety concerns in clinical settings 1,2 . Researchers recently found that physical cues in the microenvironment can control stem cell fate 3 and that particular setting can induce the osteogenesis of stem cells 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The major growth factors in bone tissue are as follows: Transforming Growth Factor β (TGF-β), Plasma-Rich Growth Factor (PRGF), acid and basic Fibroblast Growth Factor (aFGF, bFGF), and Insulin-like Growth Factor (IGF-I and IGF-II) [ 54 , 55 ]. The most important osteogenic GFs belong to the TGF-β superfamily, of which BMPs represent the most studied category, consisting of almost 18 different proteins [ 56 ].…”
Section: Biomolecules Used In In Vivo Studiesmentioning
confidence: 99%